High affinity of 4-(4-(dimethylamino)styryl)-N-methylpyridinium transport for assessing organic cation drugs in hepatocellular carcinoma cells - Metee Jinakote (2020)
© 2019 Société Française de Pharmacologie et de Thérapeutique Human organic cation transporter 1 (hOCT1) and human organic cation transporter 3 (hOCT3) are highly expressed in hepatocytes and play important roles in cationic drug absorption, distribution, and elimination. A previous study demonstrated that downregulation of hOCT1 and hOCT3 mRNA was related to hepatocellular carcinoma (HepG2) prognosis and severity. Whether these transporters expressed in HepG2 cells serve for cationic drug delivery has not been investigated. Besides radioactive transport, options for assessing hOCTs in hepatocytes are limited. This study clarified the significant roles of hOCTs in HepG2 by comparing cationic fluorescent 4-(4-(dimethylamino)styryl)-N-methylpyridinium (ASP+) with traditional [3H]-1-methyl-4-phenylpyridinium (MPP+). The results showed ASP+ was preferably transported into HepG2 compared to [3H]-MPP+ with high affinity and a high maximal transport rate. Selective transport of ASP+ mediated by hOCTs was influenced by extracellular pH, temperature, and membrane depolarization, corresponding to hOCT1 and hOCT3 expressions. Furthermore, transport of cationic drugs, metformin, and paclitaxel in HepG2 cells was blunted by OCT inhibitors, suggesting that hOCT1 and hOCT3 expressed in HepG2 cells exhibit notable impacts on cationic drug actions. The fluorescent ASP+-based in vitro model may also provide a rapid and powerful analytical tool for further screening of cationic drug actions and interactions with hOCTs, particularly hOCT1 and hOCT3 in hepatocellular carcinoma.